Examination of the Psychometric Properties of the Borderline Personality Inventory in an Adolescent Sample - Yasemin Kahya; Koret Munguldar; Melis Gün (Psikoloji Çalışmaları)
Borderline personality disorder (BPD) is a psychopathology that negatively impacts one’s interpersonal relationships. The risk of hospitalization, self-harm, and suicidality are much higher in BPD compared to other psychopathologies. Detecting BPD symptoms during adolescence and determining the necessary treatment modalities are important. The aim of the present study is to contribute to the national literature by examining the psychometric properties of the Borderline Personality Inventory (BPI) developed by Leichsenring (1999). Adolescents between the ages of 14-18 (N = 476) were reached and administered a socio-demographic form, the BPI, the Eating Attitudes Test-26 (EAT-26), and the Strengths and Difficulties Questionnaire (SDQ). The construct validity analyses indicated that the BPI was composed of the subfactors of identity and reality diffusion, volatile affect and interpersonal relationships, and impulsivity. According to the reliability analysis, Cronbach’s alpha values of internal consistency for the BPI were found to be .86 for the whole inventory and to range between .74 and .85 for each of the three subfactors. Further evidence from the construct validity analyses indicate a significant positive correlation to be present for the overall score and subfactor scores of BPI with the EAT-26 and SDQ. Thus, evidence has shown the BPI to be a reliable and valid measure for evaluating BPD symptoms in adolescents. Additionally, the relationship between the borderline symptoms evaluated using BPI and the other psychopathology symptoms supports that borderline personality features in adolescents are not a passing developmental phenomenon and are related to emotional and behavioral problems. The present study underlines the importance of interventions for symptoms before a clinical presentation turns into a personality disorder in adulthood in adolescents possessing increased borderline personality traits. The study recommends the applicability of BPI for identifying individuals with high borderline personality traits in future research and clinical practices to be conducted over adolescent samples.